Gender and food security in Honduras - Allen, Summer L.; Delgado, Luciana (International Food Policy Research Institute, 2020)
This study, supported by the Netherlands Development Organisation (SNV), obtained information on a range of topics associated with food security and nutrition, gender, and water access in selected villages of Honduras. The data collection prioritized a set of communities of interest to the civil society organizations that are part of the Voice for Change Program in Honduras. The data collection, done in 2018, covered 647 households across the departments of Choluteca, Lempira, and Ocotepeque. Most households surveyed face high levels of food insecurity. Only 26% of the women between 12 and 49 years are receiving the minimum dietary diversity. Access to water and sanitation is also limited with 30% of the households sourcing their water from a well or river and 51% not treating the water before drinking it. According to the Abbreviated Women’s Empowerment in Agriculture Index (A-WEAI) only 34% of women sampled are considered empowered. The survey results indicate that the biggest hurdles to women’s empowerment are the amount of time spent working and limited decision-making power regarding accessing credit and productive activities.